From Morning to Midnight. - Kelly, Dennis (Oberon Books, 2013)
From Morning To Midnight, among the most frequently performed German Expressionist works, charts the life of a cashier who steals money from the bank and flees to Berlin. The un-named protagonist's bid to escape his middle-class daily life is ultimately frustrated. It is a popular piece in which Kaiser satirized the cheapness and futility of modern society. His hero, a kind of machine-age Everyman, searches everywhere for some kind of fulfilment - in commercial sex, in salvationist religion - but discovers through a series of nightmarish episodes that the world is deceitful and illusory. In the end, disillusioned and pursued by the police, he takes his own life. A new version by Dennis Kelly, to play at the National's Lyttelton Theatre in November 2013, as part of the National's 50th Anniversary Season.